Genetic characterization of Callosciurus (Rodentia: Sciuridae) Asiatic squirrels introduced in Argentina - Gabrielli, María Florencia (2014)
Squirrels have been traded in the pet market for several decades, and numerous species have established in the wild. The Asiatic species Callosciurus erythraeus and Callosciurus finlaysonii have been introduced into other parts of Asia, in Europe and South America. In this study, (1) we conducted a genetic characterization of C. erythraeus introduced into Argentina and compared them with native and introduced populations in Asia, and (2) we analyzed genetic variation among the four invasion foci in Argentina in order to corroborate that the pathway of invasion was a single introduction event in the country and subsequent translocations. We analyzed mitochondrial (cytochrome b, Cyt b; cytochrome oxidase c subunit I, COI and D-loop) and nuclear (recombination activating gene I, RAGI) DNA markers using the classical method (DNA barcoding gap analysis) and also the Automatic Barcode Gap Discovery method (ABGD). The markers D-loop, COI, and RAG1 indicated that the introduced squirrels from the different invasion foci formed a monophyletic group that, together with only one haplotype for the D-loop and COI markers, supported the hypothesis of one introduction event into Argentina followed by subsequent translocations. Unexpectedly, sequences from squirrels captured in Argentina were more related to C. finlaysonii than to C. erythraeus for D-loop and Cyt b markers. However, intraspecific variation among sequences of C. erythraeus belonging to different subspecies or collected in different regions was large and comparable with the distance to the sequences from Argentina. The ABGD method also indicated large genetic variability within C. erythraeus and close proximity between squirrels from Argentina and C. finlaysonii. The complex taxonomy of Callosciurus, as occurs with the sister species C. erythraeus and C. finlaysonii, requires a thorough systematic revision. A simultaneous analysis of diagnostic morphological characters and genetic markers is needed and will provide new insight regarding the worldwide invasion of Asiatic squirrels.